Yoga Sebagai Upaya Mencapai Kesehatan Mental (Kajian Yoga Sutra Patanjali) - I Wayan Rudiarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This research aims to describe the benefits of yoga practice for mental health, especially in the Covid-19 pandemic era. This research uses qualitative research methods with literary and empirical approaches. The data obtained came from several textbooks, such as the Yoga Sutra Patanjali and several other supporting literacies, as well as phenomena that occurred in the field. During the Covid-19 pandemic, many people often experienced mental health problems, such as feelings of fear, panic, worry, anxiety and uncertain economic conditions. In a spiritual science approach, this can be overcome by applying the teachings of Yoga. The Yoga teachings were developed by Maharsi Patanjali, contained in the Yoga Sutra Patanjali and the essence of their teachings is known as asthanga yoga. In order to maintain mental health in the midst of a pandemic, proper yoga practices include the practice of asanas, pranayama and meditation. The research results showed that the practice of yoga, including asana, pranayama and meditation, was able to provide positive benefits to mental health in the midst of a pandemic, both in an effort to maintain mental health and as a form of self-healing for those with mental health disorders.Keyword : Pandemic, Mental health, Yoga.